Sistem sosial budaya masyarakat Indonesia dalam kurikulum pembelajaran Ilmu Pengetahuan Sosial tingkat menengah pertama - Rohani Rohani; Ishak Abdulhak; As'ari Djohar; M. Fahli Zatrahadi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
Education has a very close relationship to the change of values and culture, therefore in order to achieve the purity of the culture, education needs to form a strong individual person, in order to achieve a golden Indonesia by not softening existing values and cultures. Therefore, it is important to conduct this research aiming to find out the socio-cultural system of the Indonesian people in the social science learning curriculum for the junior secondary level in the province of Riau. This study uses descriptive evaluative design with mixed method type that mixed method. Purposive smpling is a sampling technique used by researchers, with several stages of data collection including: observation, interview, documentation and questionnaires. After research and results were obtained that the 2013 curriculum is better used in junior high school students compared to KTSP, by using the 2013 curriculum and a qualified strategy in the learning process can increase students' curiosity towards learning and social problems in the environment, students can understand the learning well and deeper into the value of Malay culture.